PENGARUH PEMBERDAYAAN KERJA, KARAKTERISTIK PEKERJAAN, DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN KOLAKA TIMUR - Irwan, Irwan; Adam, Pasrum; Razak, Abdul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This research aims to identify and analyze the influence of work empowerment, job characteristics, and individual characteristics on employee performance at the Office of Community and Village Empowerment in East Kolaka Regency. The sample in this study consisted of all employees at the Office of Community and Village Empowerment in East Kolaka Regency, totaling 51 people. This research employs multiple linear regression analysis. The results of the study indicate that: (1) Work empowerment, job characteristics, and individual characteristics have a positive and significant effect on employee performance at the Office of Community and Village Empowerment in East Kolaka Regency. (2) Work empowerment has a positive and significant effect on employee performance at the Office of Community and Village Empowerment in East Kolaka Regency. (3) Job characteristics have a positive and significant effect on employee performance at the Office of Community and Village Empowerment in East Kolaka Regency. (4) Individual characteristics have a positive and significant effect on employee performance at the Office of Community and Village Empowerment in East Kolaka Regency.